Supernumerary Kidney Associated with Horseshoe Malformation: A Case Report and Review of Literature - Hassan Jamshidian; Kiana Tavakoli; Faeze Salahshour; Amirreza Nabighadim; Erfan Amini (Urology Case Reports, 2017)
We report a case of supernumerary kidney associated with horseshoe malformation. A 35-year-old man presented complaining of vague and intermittent left flank pain from few months ago. Ultrasonography of urinary tract showed bilateral hydronephrosis and was suggestive of the horseshoe anomaly. Further evaluation with Intravenous urography showed three renal moieties consisting of a horseshoe kidney and a malrotated right kidney cephalad to and fused with the right moiety of horseshoe kidney.